Taḥlīlu Akhṭā’i Nuṭqi al Aṣwāti al Ṣā’itati wal Ṣāmitati fī al Qirā’ati li Ṣalāti al Janāzati li al Ṭullābi bi Ma’hadi al Iṣlāhi - Umi Azizah (Nazharat: Jurnal Kebudayaan, 2022)
This study analysis of pronunciation errors of vowels and consonants in reading the prayers of the students bodies at the al Islah boarding school. The type of research used is qualitative research.  Research whose data is obtained by studying in the field or directly in the field.  This study analyzes the vowel and consonant errors of reading the funeral prayer at the al - ishlah Islamic boarding school in Danau Pauh Jangkat, Merangin. The result of the research shows that : the causes of the errors in pronouncing vowels and consonants after using the existing theory , the mistakes made by al - islah students include : 1) .  vowel errors, long vowels become short, short vowels become long, harokat kasrah becomes dommah, and sukun becomes dommah. 2). Consonant errors, consonants.  ث،ح،ه،ص،ذ،غ،ع،ن،خ .  The solution to overcome vowel and consonant errors is by: 1). Gathering all students who are played by the teacher to give practice, in pronunciation of Arabic vowels and consonants and support.  2). Carry out activities that provide encouragement for students to be persistent in learning the pronunciation of Arabic vowels and consonants.  3). Provide direction and motivation to students.